Evaluation of Prospective Teachers in terms of their Metacognition Thinking Skills - Tuncer, Murat; Kaysi, Feyzi (Mehmet Tekerek, 2013)
In this study, it was aimed to evaluate prospective teachers in terms of their metacognition thinking skills. The study was conducted in line with the descriptive scanning model. The study was carried out on a total of 482 prospective teachers receiving education in Firat University Faculty of Education and in Istanbul University Hasan Ali Yucel Faculty of Education. Within the scope of the study, Metacognition Thinking Skills (MCTS) Scale was used as the data collection tool. Prospective teachers' opinions on metacognition thinking skills were compared in terms of their departments, genders, ages, whether they own computer, and the education faculty they attend to. In these comparisons, independent groups t test, one way variance analysis, Mann Whitney U and Kruskall Wallis H tests were employed. The findings obtained from the study indicate that there are no significant differences among the metacognition thinking skills of the prospective teachers in terms of the education faculty they attend to and the point whether or not the prospective teachers own computers. As for the gender variable, a significant difference in the Thinking skills sub factor of the MCTS scale was observed in favor of female prospective teachers. As for the comparisons made in terms of the departments where the prospective teachers receive education, significant differences in opinions were detected for the whole scale and all sub-factors. Finally, in the comparison made in terms of the age variable, significant difference was found in the Alternative evaluation skill sub factor.
Keywords: Metacognition Thinking; Prospective Teachers; Teacher Education; Cognition